Near-surface ocean dynamic off northeast Brazil and coastal sea surface salinity gradients in the world ocean - DOSSA, Alina Nathanaël (2021)
This study addresses near-surface western boundary circulation off northeast Brazil and the coastal gradient of sea surface salinity (SSS) in the world ocean. In this dissertation, we first, using conductivity temperature depth oxygen profiler (CTDO) measurements, ship-mounted acoustic Doppler current profiler (SADCP) measurements, altimetry data and numerical reanalysis products, examined the spatiotemporal variability of the North Brazil Undercurrent (NBUC) off northeast Brazil by providing an overview of the circulation, including the NBUC- NBC (North Brazil Current) transition and the potential impact of mesoscale activity. The NBUC originating south of 10S flows equatorward over the continental slope. The averag NBUC velocity, transport, and vertical extent of the velocity core were higher in spring 2015 (0.81 m/s, 15.6 Sv, and >400 m) than in fall 2017 (0.65 m/s, 11.0 Sv, and ~300 m). The orographic effect shifts the flow from northeast to south by 7.5S to northwest to north by 7.5S, following the coastline. Furthermore, this flow may be locally influenced by mesoscale activity. Further north, at ~4.8S, in the fall of 2017, the central branch of the South Equatorial Current (cSEC) entered the western boundary system where it merged with the NBUC to form the NBC, flowing toward the Caribbean Sea. In fall, the NBUC retroflection does not feed the South Equatorial Undercurrent (SEUC), which instead originates from retroflections from the cSEC and the equatorial branch of the South Equatorial Current (eSEC). Second, the mesoscale activity off Northeast Brazil (37-25W; 13-1S) was investigated using altimetry data from 1993- 2018. Approximately 1950 mesoscale eddy crossed the region, including 76% formed in the region, with amplitudes and radii ranging between 1 and 2 cm and 25 and 205 km, respectively. In the region around the Fernando de Noronha Archipelago (36-26W; 6-1S), the formation of cyclonic eddies is favored by the barotropic instability of surface currents and the wind stress curl. On the other hand, in the south of the region (36-26W; 12-8S), the formation of eddies is associated with the barotropic instability wind stress curl and surface currents meandering. Third, the analysis of coastal SSS gradients on a global scale was investigated. The objective was to assess the skills of four gridded products derived from the Soil Moisture Ocean Salinity (SMOS) and Soil Moisture Active Passive (SMAP) satellites, as well as the GLORYS global model reanalysis, to capture transboundary SSS gradients in coastal regions (300 km from the coast). These products were compared to thermosalinograph (TSG) measurements. The comparison shows various skills from one product to the other, decreasing as the coast gets closer. The satellite products generally agree better with the collocated TSG data than a global reanalysis, and show a wide range of coastal SSS gradients with different signs. In addition, the satellites reveal a global dominance of coastal cooling, mainly related to river runoff over shelves. This analysis shows a great potential of SSS remote sensing to monitor coastal processes, which would however require a jump in the resolution of future SSS satellite missions to be fully exploited.